Evaluation of Osveral efficacy in reducing ferritin levels in patients with thalassemia major - Fathi, Afshin; Vafaie, Majid; Amani, Firouz; Mohebbi, Nadia (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Beta thalassemia is one of the inherited blood diseases in which the production of specific chains in hemoglobin decreases. Esfarlal is a shaltor which is used in these patients as a single dose per day. Since it is prescribed orally, it is easier to tolerate the drug and control the serum iron level of the patient. The aim of this study was to evaluate the efficacy of Osveral in reducing ferritin levels in patients with thalassemia major. Methods: This quasi-experimental study was performed on 48 patients with thalassemia major who referred to Bu-Ali hospital for receiving blood. At the beginning of the study, the required data were collected along with patients’ tests including hemoglobin, ferritin, TSH, T4, CBC diff, BUN AST, ALT, BS and creatinine CBC diff. The Osveral drug was prescribed and the patients were evaluated monthly for up to 6 months on the basis of complications. In the first three months after the start of the drug, the serum ferritin level was measured, the dose was adjusted and 6 months after late, the previous tests were again requested, and the auditory and visual examinations were performed, and the information entered the checklist. Data were analyzed using SPSS statistical software. Results: Among all patients, 27 (56.2%) were male and the rest were women with a mean age of 22.22 ± 8.77 years. The results showed that during one year of study, hemoglobin level increased and ferritin level decreased significantly, and other parameters didn’t show significant difference. Nausea and vomiting were the most common complications among patients, which was higher after Osveral than before receiving Osveral. Conclusions: Results showed that Osveral is effective in reducing the level of ferritin in patients with thalassemia major, but control of hematuria is recommended when using this drug.